Globalization and Similarities in Corporate Governance: A Cross-Country Analysis - Khanna, Tarun; Kogan, Joe; Palepu, Krishna (The Review of Economics and Statistics, 2006)
Some scholars have argued that globalization should pressure firms to adopt a common set of the most efficient corporate governance practices, while others maintain that such convergence will not occur because of a variety of forms of path-dependence. With new data on governance in 24 developing countries as well as data on laws protecting shareholders and creditors in 49 developed and developing countries, we search for evidence that globalization is correlated with similarity in corporate governance. We find robust evidence of de jure similarity in governance. Interestingly, this is not driven by convergence to U.S. standards. Rather pairs of economically interdependent countries - especially if the countries are both economically developed - appear to adopt common corporate governance standards, even after accounting for the effects of common legal origin. In contrast to the de jure results, we find virtually no evidence of de facto similarity in corporate governance in a battery of estimations at the country, industry and firm levels. This is consistent with either the proposition that complementarities result in different national systems appropriately having different corporate governance systems, or the proposition that globalization is not strong enough to overcome local vested interests. We conclude that globalization may have induced the adoption of some common corporate governance standards but that there is little evidence that these standards have been implemented.